Occupational exposures in low- and middle-income countries: A scoping review. - Valentina Quintero Santofimio; Andre F S Amaral; Johanna Feary (PLOS Global Public Health)
Exposure to high levels of harmful agents in the workplace can significantly impact workers' health, contributing to morbidity and mortality. Levels of these exposures are often measured in high-income countries in research studies and, in some places, to monitor levels in line with health and safety regulations. However, less is known about workplace exposure levels in low- and middle-income countries (LMICs). Our aim was to describe the quantitative exposure measurements of different occupational agents across industries within LMICs. We conducted a scoping review of peer-reviewed publications available on Web of Science and PubMed from inception to 1 September 2023. Our search focused on quantitative occupational exposure measurements across industries in LMICs. We identified a total of 8,676 publications. After screening, 58 studies from 25 countries were retained for final review. China, Iran, and Tanzania contributed the greatest number of studies. Manufacturing, mining, and agriculture were the most studied sectors, with factory workers and miners being the most common job titles. Exposure measurements included vapour, gases, dust, and fumes (VGDF), solvents, metals, pesticides and particulate matter. Occupational exposure levels for the same industry varied widely across geographical regions. This review provides a comprehensive overview of occupational exposures in LMICs and highlights the absence of data in certain geographical areas and industries. The study contributes valuable insights for directing future research, and the need to optimise the assessment of occupational exposures in LMICs with the aim ultimately of reducing disease.